VARIATION IN HAEMATOLOGICAL PROFILE OF PREGNANT WOMEN ATTENDING COMBINED MILITARY HOSPITAL QUETTA - Abrar, Saidul; Lodhi, Fahad Saqib; Aman, Tauseef; Hanif, Muhammad; Shujaat, Nusrat; Abas, Hamza; Iqbal, Wasim (Journal of Ayub Medical College Abbottabad, 2019)
Background: World Health Organization recommends eight antenatal visits throughout pregnancy. Along with full blood count and fasting blood sugar tests, thirty-nine recommendations are given. The objective of this study was to find out significance of difference in haematological profile of pregnant women. Methods: This cross-sectional study on 384 pregnant women attending outpatient department of combined military hospital Quetta, Pakistan, was conducted from 1st November 2017 to 28th February 2018. Simple random sampling technique through random number table was used. Data collected through structured questionnaire from participants and their laboratory reports was grouped trimester wise. Apart from descriptive statistics, one-way ANOVA with post hoc Tukey test was used to find out significant difference at p‰¤0.05. SPSS Version 20 and MS Excel 2007 were used for data analysis and plotting graphs. Principles of research ethics were exercised. Results: Mean age (±SD) of the study participants was 27.5 (±4.8) years. Statistically significant difference was found for variables like haemoglobin, haematocrit and MCHC in different trimesters. Only 2 (0.5%) of the total participants had gestational diabetes mellitus. Conclusion: For getting normal reference ranges in our setting, large population-based studies are needed. Keywords: Pregnancy; Red cell indices; Hb; Haematocrit